The Bright, the Dark, and the Blue Face of Narcissism: The Spectrum of Narcissism in Its Relations to the Metatraits of Personality, Self-Esteem, and the Nomological Network of Shyness, Loneliness, and Empathy - Rogoza, Radosław; Żemojtel-Piotrowska, Magdalena; Kwiatkowska, Maria M.; Kwiatkowska, Katarzyna (Frontiers in Psychology, 2018)
Grandiose and vulnerable narcissism seem to be uncorrelated in empirical studies, yet they share at least some theoretical similarities. In the current study, we examine the relation between grandiose (conceptualized as admiration and rivalry) and vulnerable narcissism in the context of the Big Five personality traits and metatraits, self-esteem, and their nomological network. To this end, participants (N = 314) filled in a set of self-report measures via an online survey. Rivalry was positively linked with both admiration and vulnerable narcissism. We replicated the relations of admiration and rivalry with personality traits and metatraits—as well as extended existing knowledge by providing support for the theory that vulnerable narcissism is simultaneously negatively related to the Stability and Plasticity. Higher scores on vulnerable narcissism and rivalry predicted having fragile self-esteem, whereas high scores on admiration predicted having optimal self-esteem. The assumed relations with the nomological network were confirmed, i.e., vulnerable narcissism and admiration demonstrated a contradictory pattern of relation to shyness and loneliness, whilst rivalry predicted low empathy. Our results suggest that the rivalry is between vulnerable narcissism and admiration, which supports its localization in the self-importance dimension of the narcissism spectrum model. It was concluded that whereas admiration and rivalry represent the bright and dark face of narcissism, vulnerable narcissism represents its blue face.